Deteksi Sepsis pada Bayi Menggunakan Metode Dempster-Shafer - Waryanta, I Wayan Ryon; Putra, I Ketut Gede Darma; Purnawan, I Ketut Adi (Lontar Komputer : Jurnal Ilmiah Teknologi Informasi; Vol. 7, No. 1 April 2016DO - 10.24843/LKJITI.2016.v07.i01.p02, 2016)
S epsis be considered health problems in infants in developing countries and industrialized countries. That is because sepsis has a mortality rate that is enough high on the infants. Lack of knowledge of parents to the sepsis causing treatment too late. This study attempted to show how the Dempster-Shafer method can be used to detect Sepsis disease in Infants. Dempster-Shafer method combines Trust Value of symptoms one by one. This method is a model uncertainty with a range of probabilities. The study used six symptoms on 5 kinds of different conditions of Trust Value from any symptoms. The trials applied using the programming language PHP and HTML. The results of Dempster-Shafer for Sepsis in Infants that Condition 1 is 0.66977, Condition 2 is  0.60435, Condition 3 is 0.69249, Condition 4 is 0.66132, and the Condition 5 is 0.76756.
Keywords: Sepsis, Dempster-Shafer Method